Morphological Response Of Some Soybean Varieties On Alluvial Soil Applied By Chicken Manure - Zulaiha, Siti; Nurjani, Nurjani; Anggorowati, Dini (Jurnal Sains Mahasiswa Pertanian, 2018)
Soybean (Glycine max Linn) is a food crop as a source of raw materials of various nutritious food products. Almost all levels of society love the food made from this plant, especially in Indonesia. However, the current production of soybean has not been able to meet the domestic demand, therefore it is necessary to adjust the soybean varieties in the areas that have the potential to produce for domestic needs by providing income on the land to be used. This reseach aims to see the interaction of soybean varieties to a certain dose of chicken manure on alluvial soil. This research was conducted at Parit Husin Punggur Besar Kecamatan Sungai Kakap Kabupaten Kubu Raya Provinsi Kalimantan Barat for 3 months from October 17th 2017 to January 20nd 2018. The research used Factorial Completly Randomized Design (RAL) Design, consist of first factor 3 varieties and second factor 3 treatment dosage of chicken manure with 3 replicates and 4 plant samples. Observation variables included plant height, root volume, number of active root nodules, total dry weight, flowering time, harvest time, number of productive branches, number of pods plant, number of seeds pod, dry weight of seed plant and weight of 100 seeds of environmental observation. The result showed that there was interaction between varieties and chicken manure to observation variable of plant height 3 weeks, 4, 5 after planting, harvest time, number of pods per plant and dry weight of seed plant.Â Keywords: Chicken Manure, Soybeans, Varieties,Â